Social media posts and memes: a South African perspective on the intersection of copyright law, internet use and privacy - Mpipa, Simamkele Kuhle (University of the Witwatersrand, Johannesburg, 2023)
This research report is a reflection on the intersection of social media, privacy, dignity, and copyright law. With a click of a button, social media platforms, and the Internet at large, reveal personal information belonging to millions of individuals around the world, the digital environment has changed life as we once knew it. Legal scholars and legal practitioners must now face the novel legal issues which have been brought about the digital age. Due to the law’s reactive nature, privacy and data protection have been put at the forefront of new legislation. The subject of this paper is not data protection, rather this paper analyses the common law protection of privacy and copyright law in South Africa within the context of social media. In light of the changes brought about by the digital age, the position that I put forward in this paper is: to effectively address the challenges created by the digital environment, we must strive to adopt innovative and creative ways to use existing law rather than create new law. The paper discusses how internet memes can be harmful to the privacy and dignity of the individuals whose works they are derived from. I also examine the common law protection of privacy within this context and whether it is appropriate for addressing related issues in the digital age. Lastly, I put forward remedies in copyright law, particularly the protection of moral rights of an author, as a possible recourse that can be used by authors whose works have been made into internet memes
A research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2023
Keywords: Social media; Copyright law; Legal scholars; Legal practitioner; Memes; Internent use and privacy; UCTD; SDG-9: Industry, innovation and infrastructure